تحديد مستوى الضجيج بالعلاقة مع الغزارة المرورية في شارعين رئيسين في اللاذقية - أحمد وزان; عادل عوض; سجى أبو موسى (Tishreen University, 2019)
يهدف هذا البحث إلى دراسة العلاقة بين مستويات الضجيج المروري المكافئ و الغزارة المرورية في شارعين رئيسين في اللاذقية، للتنبؤ بمستوى الضجيج فيهما، أو في منطقة يتم تنظيمها بالعلاقة مع الغزارة المارة فيها. تمّ قياس لمستوى ضغط الصوت بشكل مباشر في أربعة مقاطع مختارة في الشارعين, وفي الوقت نفسه تمّ تعداد تصنيفي للغزارة المرورية  فيها ومن ثمّ حُسبت مستويات الضجيج الصادر عن حركة المرور، وتمّ التوصل إلى نماذج محلية تعطي مستوى  الضجيج مع الغزارة، وتبين أن نسبة المركبات ذات الضجيج المرتفع كبيرة وتتراوح بين (18-28)% وأن الضجيج في الشارعين أعلى من المستوى المسموح (67 ديسبل) ويتراوح بين (76.2-82.9) ديسبل. This research aims to study the relationship between equivalent noise level and the traffic flow in two major streets in Lattakia, for the prediction with the equivalent noise level by relation with the traffic flow. The sound pressure level has been measured directly in four passages selected at the streets. At the same time it was census classification for the vehicles. Then the noise levels equivalent was calculated for them. And it gave us local models between the equivalent noise level and the traffic flow. The study has also shown that the rate of vehicles, which has got high noise, is big and it ranges between (18-28) percent. And the noise level in these two streets is higher than the allowed noise level (67 db) and it ranges between (76.2-82.9 db)..